ASHLEY: A New Empirical Model for the High‐Latitude Electron Precipitation and Electric Field - Qingyu Zhu; Yue Deng; Astrid Maute; Liam M. Kilcommons; Delores J. Knipp; Marc Hairston (Space Weather)
Abstract In this study, a new high‐latitude empirical model is introduced, named for Auroral energy Spectrum and High‐Latitude Electric field variabilitY (ASHLEY). This model improves specifications of soft electron precipitations and electric field variability that are not well represented in existing high‐latitude empirical models. ASHLEY consists of three components, ASHLEY‐A, ASHLEY‐E, and ASHLEY‐Evar, which are developed based on the electron precipitation and bulk ion drift measurements from the Defense Meteorological Satellite Program (DMSP) satellites during the most recent solar cycle. On the one hand, unlike most existing high‐latitude electron precipitation models, which have assumptions about the energy spectrum of incident electrons, the electron precipitation component of ASHLEY, ASHLEY‐A, provides the differential energy fluxes in the 19 DMSP energy channels under different geophysical conditions without making any assumptions about the energy spectrum. It has been found that the relaxation of spectral assumptions significantly improves soft electron precipitation specifications with respect to a Maxwellian spectrum (up to several orders of magnitude). On the other hand, ASHLEY provides consistent mean electric field and electric field variability under different geophysical conditions by ASHLEY‐E and ASHLEY‐Evar components, respectively. This is different from most existing electric field models which only focus on the large‐scale mean electric field and ignore the electric field variability. Furthermore, the consistency between the electric field and electron precipitation is better taken into account in ASHLEY.